Teaching Business, Technical and Academic Writing Online and Onsite A Writing Pedagogy Sourcebook - Vengadasalam, Sarbani Sen (Cambridge Scholars Publisher, 2021)
This book grows out of the insights and proficiencies gained through teaching undergraduate and graduate students in onsite, online, and blended formats for almost three decades. Using a practitioner focus, it proffers best practices utilized and validated during the process of successfully instructing students in writing their scientific or technical proposals, professional or business reports, and academic papers or doctoral dissertations at premier American universities. The book guides facilitators through syllabus creation, discussion management, and open educational resources use, while.